Diversity of Bee Floral Resources and Honey Production Calendar in Ethiopia’s Southwest Shoa Zone - Tura Bareke; Kasim Roba; Admassu Addi (Advances in Agriculture)
Bee flora resources are essential for the development of beekeeping. This study aimed to identify the diversity of key bee forage plants, establish honey harvesting calendars, and assess different types of monofloral honey in the area. Data collection methods included a bee plant inventory, pollen collection, and honey pollen analysis. A total of 122 plant species were identified as bee plants, with 44.26% being shrubs and 27.87% being trees. These bee plants were distributed across three districts, accounting for 37.40% of the plant species, indicating a broader ecological distribution than local species. Wonchi district exhibited the highest diversity of bee plants (H′ = 4.7), followed by Waliso (H′ = 4.55). Three honey harvesting periods were identified: November, January, and June. Additionally, three distinct types of monofloral honey were produced: Erica arborea honey in January, Eucalyptus camaldulensis honey in June, and Guizotia scabra honey in November. A shortage of bee forages was noted in February, March, July, and August across all districts. The southwest Shoa zone (comprising Wonchi, Waliso, and Amaya districts) shows potential for sustainable and commercial beekeeping based on the available bee flora resources. To ensure sustainability, it is crucial to maintain the existing bee flora and increase the propagation of multipurpose plant species. Additionally, on-farm demonstrations highlighting the importance of floral and honey calendars for effective colony management are recommended.